Comparison of the conventional-rheological properties of Iraq gilsonite and SBS modified bitumen - Erkus, Yunus; Kok, Baha Vural; Yilmaz, Mehmet (Yildiz Technical Univ, 2023)
Styrene-butadiene-styrene (SBS) is widely used to improve the properties of the base bitumen and hence bituminous mixtures. As SBS modification induces cost increase, natural asphalts have become an important issue. In this study, the effects of gilsonite supplied from Iraq, a type of natural asphalt (NA) on conventional and rheological properties of bitumen, were investigated. NA was used 20%, 35%, and 50% by weight of bitumen. The properties of NA modified bitumen were compared to 2%, 3%, and 4% SBS modified bitumen. Conventional (penetration, softening point, rotational viscosity) and rheological (dynamic shear rheometer, bending beam rheometer) binder tests were conducted on base and modified bitumen. The index values representing together the workability, high and low temperature properties were defined by dividing the rutting parameter to viscosity and rutting parameter to low temperature stiffness. Overall, the test results show that 20% NA modified B160/220 bitumen exhibited similar performance with B160/220+3%SBS modification produced at 16% higher cost in terms of the high and low temperature properties.
Keywords: Bitumen; Gilsonite; SBS